Produktivkraft als Versprechen: Notwendiger Niedergang des Kapitalismus oder möglicher Kommunismus ohne viel Arbeit - Siefkes, Christian (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2016)
The ‘Fragment on Machines’ from Marx’s Grundrisse is often cited as an argument that the internal forces of capitalism will lead to its doom. But the argument that the progressive reduction of labor must doom capitalism lacks a proper foundation, as a comparison with the ‘Schemes of Reproduction’ given in Capital II shows. The latter, however, aren’t fully convincing either. In reality, more depends on the private consumption of capitalists than either model recognizes. Ultimately, most can be made of the ‘Fragment on Machines’ by reading it not as an exposure of capitalism’s internal contractions, but as a discussion of a possible communist future where labor (or work) will play but a minor role.